Evaluation of some properties of elastomeric dental impression materials after disinfection - Jawad Mohammed Mikaeel; Mustafa Kamil Namuq (Erbil Dental Journal)
Backgrounds and objectives: Dental impressions present a risk to spread infections among dental practitioners and should be disinfected to prevent the spread of these microorganisms. Different disinfectant materials and techniques can be used to eliminate this threat. The purpose of this study was to evaluate the effect of some disinfectant materials with two different techniques on surface detail and dimensional stability of elastomeric impression materials.